Pacific Island Heritage: Archaeology, Identity & Community (Terra Australis 35) - Liston, Jolie; Clark, Geoffrey; Alexander, Dwight (Terra Australis, 2011)
"This volume emerges from a ground-breaking conference held in the Republic of Palau on cultural heritage in the Pacific. It includes bold investigations of the role of cultural heritage in identity-making, and the ways in which community engagement informs heritage management practices. This is the first broad and detailed investigation of the unique and irreplaceable cultural heritage of the Pacific from a heritage management perspective. It identifies new trends in research and assesses relationships between archaeologists, heritage managers and local communities. The methods which emerge from these relationships will be critical to the effective management of heritage sites in the 21st century. A wonderful book which emerges from an extraordinary conference. Essential reading for cultural heritage managers, archaeologists and others with an interest in caring for the unique cultural heritage of the Pacific Islands".